(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the chemical composition, dry matter losses and aerobic stability of aerial part silage of araruta whit inclusion of citrus pulp and validate the forage as an alternative source of food for ruminant animals. The experimental design was completely randomized factorial scheme 3x4 (inclusion levels of additive and opening times) with five replications. The inclusion of 30% of additive promoted an increase of 8.5% in the dry matter content to the exclusive silage. Fermented silage compared to the in natura material showed a decrease of the fibrous components. The inclusion of citrus pulp and silo opening times did not influence the non-fibrous carbohydrate content. However, the additive promoted increases in total carbohydrate content of silages. There was no statistical difference for effluent and gas losses. Silage only including 30% citrus pulp had the lowest dry matter recovery. The average maximum temperature reached by the silages was 34.5ºC. The average time for temperature increase was 67 hours for all silages. Aerial part silage of araruta can be used in animal feed, and is a potential forage resource for use in semiarid region.